ASYLUM AND SAFE COUNTRY POLICIES IN EUROPE: LESSONS FOR THE DEBATE ON THE DESIGNATION OF MEXICO AND GUATEMALA AS THIRD SECURE COUNTRIES - Crowhurst Pons, Felipe Ignacio (Revista de Historia Social y de las Mentalidades, 2020)
The following article analyses the conceptual and historical development of safe country policies in Europe since the 1980s. The article discusses the main issues associated with the creation and use of safe country policies as instruments for declaring inadmissible or dismissing the merits of an asylum claim. Although the European countries sought to streamline asylum procedures by designating more countries as safe, these efforts have failed because the execution and coordination of safe country policies are also convoluted and time consuming. In the light of the European experience, the article concludes that the US objective of labelling Mexico and Guatemala as safe third countries will hardly release pressure from their asylum system due to practical difficulties that Europe’s experience has shown from a long time ago.